Electrical Conductivity of Water Treated by Spark Discharge - Alexander Anatolievich Belov; Alexey Nikolayevich Vasilyev; Andrey Anatolievich Musenko (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
Electrical conductivity is an electrophysical characteristic, which is considered to be an estimate of the ability of substances to miss electrical current. Achieving the result of the formation of electrohydraulic discharges in water directly depends on the magnitude of the electrical conductivity, which argues the relevance of the topic. The paper presents the results of a study of the influence of electrohydraulic treatment on the change in the electrical conductivity of water. As a result of identifying significant factors influencing the process, rational parameters of the technological mode of electrohydraulic treatment of distilled, lake and tap water were selected. Curves of functional dependences of electrical conductivity on the number of spark high-voltage pulsed discharges are constructed. The relationship between the electrical conductivity of water and the modes of electrohydraulic effects is established.